2023
DOI: 10.3390/ijms24076139
|View full text |Cite
|
Sign up to set email alerts
|

Infectious Recombinant Senecavirus A Expressing p16INK4A Protein

Abstract: Senecavirus A (SVA) is an oncolytic RNA virus, and it is the ideal oncolytic virus that can be genetically engineered for editing. However, there has not been much exploration into creating SVA viruses that carry antitumor genes to increase their oncolytic potential. The construction of SVA viruses carrying antitumor genes that enhance oncolytic potential has not been fully explored. In this study, a recombinant SVA-CH-01-2015 virus (p15A-SVA-clone) expressing the human p16INK4A protein, also known as cell cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Importantly, SVV has demonstrated anti-tumor capacity when administered systemically, leading to an extent of survival in an orthotopic medulloblastoma cancer model [63]. eSVV's reverse genetics have allowed the insertion of exogenous therapeutic payloads that can enhance the oncolytic activity of SVV-001 [66]. In the study conducted by Wencheng et al, an oncolytic SVV-A codifying p16 INK4A protein, also known as cell cycle-dependent protein kinase inhibitor 2A (CDKN2A), was rescued and characterized [66].…”
Section: Seneca Valley Virus (Svv)mentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, SVV has demonstrated anti-tumor capacity when administered systemically, leading to an extent of survival in an orthotopic medulloblastoma cancer model [63]. eSVV's reverse genetics have allowed the insertion of exogenous therapeutic payloads that can enhance the oncolytic activity of SVV-001 [66]. In the study conducted by Wencheng et al, an oncolytic SVV-A codifying p16 INK4A protein, also known as cell cycle-dependent protein kinase inhibitor 2A (CDKN2A), was rescued and characterized [66].…”
Section: Seneca Valley Virus (Svv)mentioning
confidence: 99%
“…eSVV's reverse genetics have allowed the insertion of exogenous therapeutic payloads that can enhance the oncolytic activity of SVV-001 [66]. In the study conducted by Wencheng et al, an oncolytic SVV-A codifying p16 INK4A protein, also known as cell cycle-dependent protein kinase inhibitor 2A (CDKN2A), was rescued and characterized [66]. The results showed that SVA-p16 had significantly stronger antitumor effects than the unmodified SVA virus in the human oligodendroglioma Ishikawa cell line.…”
Section: Seneca Valley Virus (Svv)mentioning
confidence: 99%